gabeye
Answered

Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

p+h= 43
4.5p+12h=276


Sagot :

9514 1404 393

Answer:

  (p, h) = (32, 11)

Step-by-step explanation:

We can write an expression for p using the first equation, then substitute that into the second equation.

  4.5(43-h) +12h = 276 . . . . substitute for p

  193.5 +7.5h = 276 . . . . . . eliminate parentheses

  7.5h = 82.5 . . . . . . . . . . . . subtract 193.5

  h = 82.5/7.5 = 11 . . . . . . . . divide by the coefficient of h

  p = 43 -11 = 32

The solution is (p, h) = (32, 11).